The PAYE sector's perspective of taxation and trade union demand for reform - Sweeney, Paul (Statistical and Social Inquiry Society of Ireland, 1984)
I would like to thank the Statistical Society for inviting me to speak on the subject of taxation. It is a very broad area and I will take the opportunity to attempt to show the PAYE sector's perspective of taxation, why the large demonstrations took place, why they may recur, and outline the trade union demands for reform. It is now over ten years since the first calls were articulated for a more equitable taxation system. These calls were not translated into action until five years ago, and since the protests began, the tax system has actually become more regressive. In spite of the largest mass protest ever seen in the country, the four alternate governments since then have shown themselves to be unconcerned with reform and have been unwilling to bend to the will of a majority of those at work.
Symposium on Taxation
Read before the Society, 2 November, 1983
Keywords: Income tax; PAYE; 314.15